The efficiency of control tests for the evaluation of multilateral physical training in advanced level 14-15 year old female athletes - Scurt, C. (Annals of "Dunarea de Jos" University of Galati: Physical Education and Sport Management, 2020)
The research hypothesis starts from the premise that the efficiency of using the evidence of verifying the multilateral physical training is a useful method for advanced level female athletes. The aim of the research is to improve the means of training and the structure of the competitive calendar by restructuring the training to obtain the optimal sports form in the competition of objectives. The topic of the research is represented by the methods and means of training as well as the structure of the competitive calendar. The practical value of the research consists in the possibility to elaborate training models that are useful to the specialists in the field.